Multiple AV Nodal Pathways in Patients with AV Nodal Reentrant Tachycardia More Common than Expected - Abbas, Saleha; Cheema, Ammar Azam (Indus Journal of Bioscience Research, 2025)
Introduction: Atrioventricular nodal reentrant tachycardia (AVNRT) is an established septal arrhythmia considered to rise from dual nodal AV pathways. However, the fact that there are multiple pathways within the AV node has not received much attention. Objectives: To investigate the prevalence and clinical significance of multiple AV nodal pathways in patients with AVNRT, utilizing advanced electrophysiological techniques. Materials and Methods: This descriptive study was carried out at the Punjab Institute of Cardiology Lahore during the year of January 2023 to December 2023. Electrophysiological studies and electrophysiological mapping catheter ablation were done on 200 patients. Demographic, clinical, and procedural information were used and scrutinized to determine additional AV nodal pathways. Results: AV nodal pathways were found to be multiple in 38 per cent of patients. This group had a noticeably prolonged VA interval, increased conduction variability, and longer ablation times as well. The success rate in obtaining ablation was higher at 96%, and complications were few, but procedural AF was more complex in patients with multiple pathways. Conclusion: It is concluded that Multiple AV nodal pathways are more prevalent than previously recognized, influencing diagnostic and therapeutic strategies for AVNRT.